EPIDERMOLYSIS BULLOSA IN THE NEWBORN - Mohammad, Nadia; Sohaila, Arjumand; Hussain, Ali Akhter; Ani, Shumaila (Journal of Ayub Medical College Abbottabad, 2016)
We present the case of a new-born baby girl who was delivered at term to a young primigravida mother. The pregnancy was booked late and had no antenatal medical or surgical complications. The baby was born vaginally and had a normal initial examination. However after three hours of birth the baby started to develop skin blisters after minor trauma/friction. The baby was seen by a Dermatologist who diagnosed the condition to be Epidermolysis Bullosa. This hereditary condition is extremely rare, and even rarer is such an early presentation in a neonate. It is caused by mutations in the genes coding for the structural proteins of the skin and is characterized by development of vesicles and blisters. The mainstay of management is supportive care. The baby was discharged on request of the parents on second day of life without any complications.